Diastereo‐ and Enantioselective Synthesis of Bisbenzannulated Spiroketals and Spiroaminals by Ir/Ag/Acid Ternary Catalysis. Issue 42 (19th August 2022) - Yang, Wu‐Lin; Shang, Xin‐Yu; Ni, Tao; Yan, Hui; Luo, Xiaoyan; Zheng, Hanliang; Li, Zhong; Deng, Wei‐Ping
Abstract: We reported herein an iridium/silver/acid ternary catalytic system to access bisbenzannulated [6, 6]‐spiroketals in high efficiency with generally high diastereo‐ and enantioselectivities (up to >20 : 1 dr, >99 % ee). In this procedure, readily available o ‐alkynylacetophenones undergo cycloisomerization to generate isochromenes in situ that participate in stereoselective allylation/spiroketalization sequence with 2‐(1‐hydroxyallyl)phenols. Meanwhile, 2‐(1‐hydroxyallyl)anilines were also compatible in this cascade reaction, furnishing structurally novel bisbenzannulated [6, 6]‐spiroaminals with good diastereoselectivities (8 : 1–12 : 1 dr) and excellent enantioselectivities (98 %–>99 % ee). Moreover, experimental studies and theoretical calculations were performed to illustrate the reaction mechanism and stereochemistry. Abstract : A cycloisomerization/asymmetric allylation/spiroketalization cascade reaction of o ‐alkynylacetophenones and (1‐hydroxyallyl)phenols enabled by Ir/Ag/acid ternary catalysis was developed, affording structurally diverse bisbenzannulated [6, 6]‐spiroketals in high efficiency with mostly high diastereoselectivities and excellent enantioselectivities.